The Effect Of Budget Management And Transparency On Financial Performance At The Audit Board Of The Republic Of Indonesia Representative Office Of North Sumatra Province - Annisa Larasati; Geby Citra Ananda; Aullia Aulia (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the effect of budget management and transparency of public financial information disclosure on financial performance at the Audit Board of the Republic of Indonesia (BPK RI) Representative Office of North Sumatra Province. This research employs a quantitative approach with descriptive and associative research designs. The data used in this study are secondary data obtained from financial statements and performance reports of BPK RI Representative Office of North Sumatra Province for the period 2020–2024. Budget management is measured using the budget effectiveness ratio, transparency is assessed based on the availability and accessibility of financial information, while financial performance is measured using liquidity ratios.